Mastite subclínica causada por Staphylococcus aureus: Custo-benefício da antibioticoterapia de vacas em lactação - Zafalon, L. F.; Nader Filho, A. [UNESP]; Oliveira, J. V.; Resende, F. D. (FapUNIFESP (SciELO), 2007)
Economic evaluation of the treatment bovine subclinical mastitis caused by S. aureus was evaluated. Two hundred and seventy udder quarters with or without subclinical mastitis were distributed into four groups, in conformity to lactational stage and treatments. Group 1 included animals treated between 10 and 60 days of lactation; group 2 included animals treated from 61 days of lactation to two months before drying; group 3 included animals no treated between 10 and 60 days of lactation; group 4 included animals no treated from 61 days of lactation to two months before drying. Treatment with gentamicin (150mg) was accomplished by intramammary doses, once a day, after performing sensitivity tests. The mammary quarters were re-evaluated after 30 days. The costs with the treatment were calculated considering a S. aureus prevalence of 5% as well as expenses with antibiotic, milk disposal, tests of drug sensitivity and workload. There was loss of income of 2% and 14% in the groups 1 and 2, respectively, when compared with the values before the treatment. In such case, the treatment of bovine subclinical mastitis caused by S. aureus in the lactation was economically unviable.
Subclinical mastitis caused by Staphylococcus aureus: Cost benefit analysis of antibiotic therapy in lactating cows
Keywords: Antibiotic; Costs; Staphylococcus aureus; Subclinical mastitis; Treatment; Animalia; Bovinae